2012
DOI: 10.1186/1471-2458-12-101
|View full text |Cite
|
Sign up to set email alerts
|

Why is high-risk drinking more prevalent among men than women? evidence from South Korea

Abstract: BackgroundIt is important to identify and quantify the factors that affect gender differences in high-risk drinking (HRD), from both an academic and a policy perspective. However, little is currently known about them. This study examines these factors and estimates the percentage contribution each makes to gender differences in HRD.MethodsThis study analyzed information on 23,587 adults obtained from the Korea National Health and Nutrition Surveys of 1998, 2001, and 2005. It found that the prevalence of HRD wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…Similarly to previous research studies, this study showed that men in Serbia and Hungary are more likely to consume alcohol compared to women, which can be related not only to the cultural heritage and the generally accepted model of behaviour, but also to the greater economic power of men. Evidence suggests that the gender gap in socio-economic status is significant between the two countries [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to previous research studies, this study showed that men in Serbia and Hungary are more likely to consume alcohol compared to women, which can be related not only to the cultural heritage and the generally accepted model of behaviour, but also to the greater economic power of men. Evidence suggests that the gender gap in socio-economic status is significant between the two countries [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Despite betel nut and cigarette consumption, the prevalence of alcohol consumption is similar to Germany and South Korea. Donath et al [21] found higher alcohol consumption in rural than urban areas in Germany, and Chung et al [22] found that of the males, 90% are likely to drink excess alcohol in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that it is not only the male gender that is associated with these 3 kinds of behavior [22,25], but that socioeconomic inequalities are important [10,26,27], with poor education, low economic status and living in rural areas being associated with ABC use [21,26]. Our findings indicate that 4.5% (122) of alcohol, 13.4% (360) of betel nut, and 13.3% (357) of cigarette users reported abstinence for >1 year.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Highrisk drinking was defined as drinking >60 g pure alcohol per drinking day for men and >40 g per drinking day for women. 14 Individuals with household incomes in the lowest quartile were designated as the low-income group. The education level was classified as low if the respondent did not finish education beyond middle school (higher than ninth grade).…”
Section: Demographic Variablesmentioning
confidence: 99%
“…The World Health Organization Community Periodontal Index (CPI) was used to assess periodontal treatment needs and defined participants with periodontal treatment needs as CPI code ‡3. 18,19 A CPI score of code 3 indicates that ‡1 site had a >3.5-mm pocket in the index teeth, which are 2, 3,8,14,15,18,19,24,30, and 31 according to the Universal Numbering System adopted by the American Dental Association.…”
Section: Periodontal Treatment Needsmentioning
confidence: 99%